2015
DOI: 10.1002/adom.201400635
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Plasmene Nanosheets as Soft and Surface‐Attachable SERS Substrates with High Signal Uniformity

Abstract: COMMUNICATIONstronger than those obtained from a commercial Klarite SERS substrate, which was rigid, opaque, and could not be used for direct chemical identifi cation on banknotes or coins.A combination of polymer-ligand-based strategy and dryingmediated air-water interfacial self-assembly was utilized for the fabrication of plasmene nanosheets with Au@Ag nanocubes (NCs) as model building blocks. [7][8][9] The physical steps towards obtaining a free-standing plasmene nanosheet are demonstrated in Figure 1 a. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 38 publications
1
85
0
Order By: Relevance
“…S7, the Raman spectra of 4-ATP can be clearly observed for all three pyramids. The observed peaks can be assigned in accordance to the literature [2], in which the two evident 1078 and 1388 cm -1 peaks that are enhanced by electromagnetic enhancement are assigned to the C-S stretching, and C-C stretching modes, respectively. The weaker peaks at 1141, 1392 and 1438 cm -1 are attributed to the weak charge transfer mechanism from Au-S bonds.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…S7, the Raman spectra of 4-ATP can be clearly observed for all three pyramids. The observed peaks can be assigned in accordance to the literature [2], in which the two evident 1078 and 1388 cm -1 peaks that are enhanced by electromagnetic enhancement are assigned to the C-S stretching, and C-C stretching modes, respectively. The weaker peaks at 1141, 1392 and 1438 cm -1 are attributed to the weak charge transfer mechanism from Au-S bonds.…”
Section: Resultssupporting
confidence: 67%
“…5, the plot of the SERS intensity for the dominant 1078 cm -1 peak revealed that RD pyramid exhibited the strongest SERS signal, followed by OH and NS pyramid. The enhancement factors, as calculated in accordance to the classical equation [2,34], were found to be 1.8 9 10 7 , 5.3 9 10 6 and 1.9 9 10 6 for RD, OH and NS pyramids, respectively (see Supplementary Information Part SIV for calculation). This trend can be explained according to the electromagnetic theory and lightning rod effect, in which building blocks with sharp features are expected to be able to support higher electromagnetic field intensities due to the concentrated electromagnetic field within the regions of curvature [46,47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations